1992
DOI: 10.1002/aic.690381109
|View full text |Cite
|
Sign up to set email alerts
|

Predictive correlation for binary diffusion coefficients in dense carbon dioxide

Abstract: Binary diffusion coefficients of some organic compounds in carbon dioxide at 313.2 K and 16.0/25.0 MPa were measured by using the Taylor-Aris tracer response technique. We propose a new correlation of Schmidt numbers as a function of solvent molar volumes for predicting binary diffusion coefficients in dense C 0 2 and self-diffusion coefficients of dense C 0 2 . The correlation was also found to be valid for predicting self-diffusion coefficients of dense CH, at F,/A* <40 or u2/ ( 4 ) 0 > 1.62.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(58 citation statements)
references
References 36 publications
1
55
2
Order By: Relevance
“…where N AV is Avogadro number and v 0 was calculated from the equation proposed by Funazukuri et al [17]. The effective hard-sphere diameter of solute(2) was calculated by σ σ σ σ (8) where σ vw is the van der Waals diameter estimated by the method of Bondi [18].…”
Section: Correlationmentioning
confidence: 99%
“…where N AV is Avogadro number and v 0 was calculated from the equation proposed by Funazukuri et al [17]. The effective hard-sphere diameter of solute(2) was calculated by σ σ σ σ (8) where σ vw is the van der Waals diameter estimated by the method of Bondi [18].…”
Section: Correlationmentioning
confidence: 99%
“…Data at 333.15 and 343.15 K, excluding those deviating from the background values (marked with "a" in Table 1). 12 and myristic acid ethyl ester (X, 308, 313 and 318 K) in the literature. 13 The legend for the present data is the same as in Fig.…”
Section: 13mentioning
confidence: 99%
“…22 Figure 2 shows the D12/T vs. CO2 viscosity for (a) myristoleic acid, and (b) myriostoleic acid methyl ester measured in this study and a previous study, 12 together with the literature data of myristic acid ethyl ester. 13 The D12 values in the latter two studies 12,13 were measured by the Taylor dispersion method. We have demonstrated the validity of the correlation in the following equation for a variety of compounds:…”
mentioning
confidence: 99%
“…1) Advantages of supercritical fluid extraction include favourable mass transport properties and minimisation of waste solvent generation. 4) A number of studies have demonstrated the extraction of metal ions present in aqueous solutions by supercritical CO 2 , but understanding of the rate of the extraction process is often unknown. 2,[5][6][7][8][9] The feasibility of extracting uranyl ions from nitric acid solutions may have important applications in nuclear waste management.…”
Section: Introductionmentioning
confidence: 99%